Anti-Inflammatory Effects of Thymoquinone in Atherosclerosis: A Mini Review - Leong, Xin-Fang; Choy, Ker Woon; Alias, Aspalilah (Frontiers in Pharmacology, 2021)
Atherosclerosis poses serious health problems and increases the risk of various cardiovascular diseases, including myocardial infarction, heart failure, ischemic stroke, and peripheral arterial disease. Atherosclerosis patients require long-term medications to prevent complications, some of which are costly and may result in unwanted adverse reactions. Natural products have emerged as potential sources of bioactive compounds that provide health benefits in cardiovascular diseases. Increased inflammation and vascular remodeling have been associated with atherosclerosis pathogenesis. The molecules involved in signaling pathways are considered valuable targets for new treatment approaches. Therefore, this review aims to summarize the available evidence of the anti-inflammatory effects of thymoquinone, the major active compound isolated from Nigella sativa L., via inflammatory signaling pathways in atherosclerosis. Specifically, nuclear factor-κB and mitogen-activated protein kinase signaling pathways were considered. Furthermore, the potential toxic effects elicited by thymoquinone were addressed. These findings suggest a potential role of thymoquinone in managing atherosclerosis, and further studies are required to ascertain its effectiveness and safety profile.